Chitosan processing waste nutrients compounds as a potential natural poultry premix. - Hertamawat, Rosa Tri; Imam , Shokhirul; Rahmasari, Reikha; Suryadi, Ujang (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to use the potential chitosan processing waste from shrimp heads as a premix to improve the production performance of laying chickens. Materials and Methods: This research uses shrimp head waste, NaOH, hydrochloric acid, Na2SeO3, and NaCl solutions. Processing shrimp head waste into chitosan is done in three ways, namely demineralization, deproteination, and deacetylation. Each of the resulting liquid wastes is then mixed until a neutral mixture is obtained. The data observed were the nutrient and amino acid content of liquid waste from the deproteinization, demineralization, and deacetylation processes, as well as the neutral mixture. Results: The results showed liquid waste from the process of making chitosan from shrimp head waste using deproteination, demineralization, and deacetylation methods, as well as a neutral mixture containing little energy, protein, and fat but is rich in minerals. The most abundant and complete amino acid content is found in deproteination process wastewater and neutral mixtures. Conclusion: In conclusion, the waste from making chitosan from shrimp head waste through deproteinization, demineralization, and deacetylation, and the neutral mixture contains enough minerals and amino acids needed by livestock, so it has the potential to be used as a premix. J. Adv. Vet. Anim. Res., 12(1): 117–122, March 2025 http://doi.org/10.5455/javar.2025.l878